IMPLEMENTASI TEKNOLOGI TEPAT GUNA: KAJI TERAP MESIN PENCACAH PLASTIK UNTUK PENGOLAHAN SAMPAH SKALA KOMUNITAS - Sujana, Ivan; Imansyah, Fitri (Universitas Mataram, 2025)
Plastic waste is a growing environmental issue, particularly in community-level areas that lack adequate waste management systems. This community service activity aims to implement appropriate technology in the form of a plastic crusher machine to support efficient, economical, and sustainable plastic waste processing at the community scale. The method includes community needs assessment, machine design and fabrication, operational training, and post-implementation monitoring and evaluation. The results show that the crusher machine can reduce the volume of plastic waste by up to 60% and significantly increase community participation in waste management activities. Furthermore, this machine has the potential to drive recycling-based economic activities through the utilization of crushed plastic waste as raw material for new products. This program contributes directly to enhancing local community capacity in addressing environmental problems and promotes self-reliant waste management through the application of appropriate technology.